What factors determine the pregnancy outcome in patients with essential thrombocythemia?. (17th December 2022) - Kwiatkowski, Jacek; Kuliszkiewicz-Janus, Małgorzata; Potoczek, Stanisław; Jaźwiec, Bożena; Wróbel, Tomasz; Małecki, Rafał
Abstract: Objectives: Treatment of essential thrombocythemia (ET) is particularly challenging in pregnancy due to the increased risk of thromboembolic complications. Therefore, the use of antithrombotic regimens are recommended in pregnant women with ET. Methods: The study included 52 pregnancies in 27 patients diagnosed with ET, who were treated in Department of Haematology. The influence of anticoagulant, antiplatelet and cytoreductive therapy on the course and outcome of pregnancy was analysed. This study also examined if there was any correlation between molecular and clinical features such as mutational profile, blood count, presence of acquired von Willebrand syndrome (AvWS), the International Prognostic Score for Essential Thrombocythemia (IPSET) risk group and the IPSET-thrombosis risk group and pregnancy outcome. Results: Study participants who received antithrombotic therapy were significantly more likely to give birth to a healthy child. The best outcomes were observed in patients who received low dose acetylsalicylic acid (ASA) together with low-molecular-weight heparin (LMWH). There was a statistically significant correlation between classification to the high-risk group according to the IPSET-thrombosis score and incidence of miscarriage. Cytoreductive treatment with interferon-α2, as well as the presence of AvWS did not increase the likelihood of pregnancy loss. Blood counts and presence of specific gene mutations profile were also not found to be significant determinants of pregnancy outcome. Conclusion: To our best knowledge, this is the first clinical study investigating the correlation between risk group (according to IPSET and IPSET-thrombosis) and pregnancy outcome in women with ET.